Political violence from the extreme right in contemporary Portugal - Marchi, R.; Da Silva, R. (Perspectives on Terrorism, 2019)
In Portugal, extreme right political violence can be found in two different periods: in the period of transition from authoritarianism to democracy (between 25 April 1974 and the mid1980s) and from the second half of the 1980s, leading up to the present. In the first period, militants who had been radicalised by the Colonial War (1961-1974), by the anti-imperialist mobilisation of the extreme left student movement in the academic crises of the 1960s, but also by the actions of the revolutionary leadership of the transition process after the April Revolution, were active in politically violent organisations aimed at stopping the advance of communism in Portugal. Among these organisations, the ELP (Exército de Libertação de Portugal /Portugal Liberation Army) gained salience and will be explored in-depth in this chapter. The second period was characterised by a new extreme right showcasing an ethnonationalist political identity and discourse, which fused both the ultra-nationalism of the old extreme right and the neo-Nazi racism of the skinhead subculture. Initially, the MAN (Movimento de Acção Nacional / National Action Movement) was key in uniting the nationalist militants and the skinheads. After its dismantling by the authorities, it was replaced by the PHS (Portugal Hammer Skin). The dynamics of both organisations will be explored in detail throughout this chapter. For this, the research uses a qualitative methodology based on interviews carried out with extreme right militants, on documentation produced by the different movements and on archive material produced by the police and court investigations.